THE STUDY OF THE PEDAGOGICAL ASSESSMENT INDICATORS OF READING DIFFICULTY IN 6-11-YEAR-OLD STUDENTS WITH DYSLEXIA - Shashviashvili, Maia; Melikishvili, Manana; Kitiashvili, Zakaria (Georgian Psychological Journal, 2024)
The study presented in the paper was motivated by the fact that there was no checklist available in the Georgian educational space for assessing reading difficulties (dyslexia) that would allow for the early identification of this problem. As part of the study, we reviewed 11 forms (checklists) of dyslexia assessment indicators used in the educational systems of various countries. These checklists are intended for teachers, parents, school psychologists, and students, and serve the identification of reading difficulties. Since the purpose was to develop a checklist of indicators for assessing reading difficulties (dyslexia) specifically for teachers, we selected relevant questions designed for educators and based our analysis on them to create an assessment tool. The study was conducted at Tbilisi Public School # 173, the “International Academy Logos,” and “Tbilisi Free School.” Additionally, with the support of the “Association of Special Educators”, the form for assessing reading difficulties (dyslexia) indicators was completed by special educators working in schools in Tbilisi and the regions. Various school teachers participated in the study via social media. Furthermore, 305 students participated in the study, of which 98 have dyslexia. Data processing was carried out using SPSS 23. It was confirmed that with the use of our checklist of 49 dyslexia assessment indicators, it is possible to identify the 6-11-yearold students (from the first to the fifth grade) who have dyslexia or reading difficulties.